Reliability and Validity of SymTrak, a Multi-Domain Tool for Monitoring Symptoms of Older Adults with Multiple Chronic Conditions - Monahan, Patrick O. (J Gen Intern Med, 2019)
BACKGROUND: A reliable and valid clinically practical multi-domain self-report and caregiver-report tool is needed for tracking actionable symptoms in primary care for elderly patients with multiple chronic conditions (MCCs). OBJECTIVE: Assess internal consistency reliability, test–retest reliability, construct validity, and sensitivity to change for SymTrak. DESIGN AND PARTICIPANTS: Among 600 (200 patient–caregiver dyads, 200 patients without an identified caregiver) participants, SymTrak was telephone interviewer–administered at baseline and 3-month follow-up, and at 24 h post-baseline for assessing test–retest reliability in a random subsample of 180 (60 dyads, 60 individual patients) participants. MAIN MEASURES: Demographic questions, SymTrak, Health Utility Index Mark 3 (HUI3). KEY RESULTS: Exploratory factor analysis indicated a single dominant dimension for SymTrak items for both patients and caregivers. Coefficient alpha and 24-h test–retest reliability, respectively, were high for the 23-item SymTrak total score for both patient-reported (0.85; 0.87) and caregiver-reported (0.86; 0.91) scores. Construct validity was supported by monotone decreasing relationships between the mean of SymTrak total scores across the poor-to-excellent categories of physical and emotional general health, and by high correlations with HUI3 overall utility score, even after adjusting for demographic covariates (standardized linear regression coefficient = − 0.84 for patients; − 0.70 for caregivers). Three-month change in the SymTrak total score was sensitive to detecting criterion standard 3-month reliable change categories (Improved, Stable, Declined) in HUI3-based health-related quality of life, especially for caregiver-reported scores. CONCLUSIONS: SymTrak demonstrates good internal consistency and test–retest reliability, construct validity, and sensitivity to change over a 3-month period, supporting its use for monitoring symptoms for older adults with MCCs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-018-4780-4) contains supplementary material, which is available to authorized users.